Dampak Kekerasan Verbal Orang Tua Pada Perkembangan Sosioemosional Anak Usia Dini - Sari, Elina Novita; Syafrudin, Ulwan; Yulistia, Annisa (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2024)
Verbal abuse by parents significantly impacts the socio-emotional development of early childhood. At this critical age, children build their self-confidence and social relationships. This study aims to examine the effects of verbal abuse on children’s emotional, social, and cognitive aspects. The research employs a qualitative method, utilizing in-depth interviews, observations, and case study analysis. Findings reveal that children exposed to verbal abuse are at high risk of emotional disturbances such as anxiety, depression, and insecurity, leading to social withdrawal and poor academic performance. Moreover, verbal abuse damages parent-child relationships and hinders the development of children’s communication skills. The study concludes with a call for parents to foster a positive and supportive environment for their children. Recommendations include raising parental awareness and education to prevent verbal abuse and promote healthy child development.